Different miR‐21‐3p isoforms and their different features in colorectal cancer. Issue 10 (2nd August 2017) - Jiao, Weijuan; Leng, Xueqin; Zhou, Qun; Wu, Yayun; Sun, Lina; Tan, Yan; Ni, Hengli; Dong, Xiaoqiang; Shen, Tong; Liu, Yao; Li, Jianming
Abstract : MiR‐21, the only microRNA (miRNA) found to be overexpressed in any type of solid tumor, its guide stand, miR‐21‐5p, has been studied a lot in colorectal cancer (CRC); however, few researchers focused on its passenger strand, miR‐21‐3p. In our study, based on The Cancer Genome Atlas (TCGA) data, we found that there were more varieties and quantities of miR‐21‐3p isoforms in microsatellite instability (MSI)‐type CRC. We further examined the role of miR‐21‐3p by in vitro and in vivo studies. MiR‐21‐3p may be an oncogene in CRC by promoting cellular mobility through epithelial–mesenchymal transition. However, different isoforms, especially miR‐21‐3p 0 | 2, may be a favorable prognostic marker for CRC survival, probably due to increased complementary effect of miR‐21‐5p and/or target genes. Further study investigating the underlying mechanism of miRNA isoforms is needed. Abstract : What's new? MicroRNAs (miRNAs) play a vital role in many malignancies, including colorectal cancer (CRC). Two forms of miR‐21 miRNAs have been implicated in CRC: "miR‐21‐5p" (called the "guide strand") and "miR‐21‐3p" (called the "passenger strand"). Higher levels of miR‐21‐5p may predict tumor relapse and poor survival. On the other hand, miR‐21‐3p and its variants are not well understood. In our study, the authors analyzed the role of miR‐21‐3p isoforms in CRC and found that they may also affect prognosis. Further study is needed to clarify the molecular mechanisms involved.